Bcl-xL activity influences outcome of the mitotic arrest - Suleimenov, M.; Bekbayev, S.; Ten, M.; Suleimenova, N.; Tlegenova, M.; Nurmagambetova, A.; Kauanova, S.; Vorobjev, I. (Frontiers in Pharmacology, 2022)
Microtubule targeting (MT) drugs taxanes and vinca alkaloids are widely used as chemotherapeutic agents against different tumors for more than 30 years, due to their ability to block mitotic progression by disrupting the mitotic spindle and activating Spindle Assembly Checkpoint (SAC) for prolonged period of time. However, responses to mitotic arrest are different - some cells die during mitotic arrest while others undergo mitotic slippage and survive becoming able for proliferation. Using normal fibroblasts and several cancer cell types we determined two critical doses T1 and T2 of mitotic inhibitors (Nocodazole, Taxol and Vinorelbine). T1 is the maximal dose cells can tolerate undergoing normal division and T2 is the minimal mitostatic dose, wherein >90% mitotic cells are arrested in mitosis. In all studied cell lines after treatment with mitotic inhibitors in a dose above T2 cells had entered mitosis either die or undergo mitotic slippage. We show that for all three drugs used cell death during mitotic arrest and after slippage proceeded via mitochondria-dependent apoptosis. We determined two types of cancer cells – sensitive to mitotic arrest, i.e. undergoing death in mitosis (DiM) frequently, and resistant to mitotic arrest, i.e. undergoing mitotic slippage followed by prolonged survival. We then determined that inhibition of Bcl-xL, but not other anti-apoptotic proteins of Bcl-2 group that regulate MOMP, make resistant cells susceptible to DiM induced by mitotic inhibitors. Combined treatment with MT drugs and highly specific Bcl-xL inhibitors A-1155643 or A-1331852 allows achieving 100% DiM in a time significantly shorter than maximal duration of mitotic arrest in all types of cultured cells tested. We further examined efficacy of sequential treatment of cultured cells using mitotic inhibitors followed by inhibitors of Bcl-xL anti-apoptotic protein and for the first time show that sensitivity to Bcl-xL inhibitors rapidly declines after mitotic slippage. Thus sequential use of mitotic inhibitors and inhibitors of Bcl-xL anti-apoptotic protein will be efficient only if Bcl-xL inhibitor will be added before mitotic slippage occurs or soon afterwards. The combined treatment proposed might be an efficient approach to anti-cancer therapy.